Scaling Globalization: The Circulation of Language Resources in Two Indonesian Global Social Movements - Azyyati, Nurina; Kusuma, Dwi Linda; Kurniati, Nurul Adha (Journal of Pragmatics and Discourse Research, 2024)
This study explores two social movements in Indonesia to measure the extent to which the locals mobilize towards the center. This objective departs from two contradictory statements, namely 'Global Language' (Crystal, 2003; see also the issue of Linguistic Imperialism) which argues that globalization always moves towards the center and produces uniformity, and another statement which argues that globalization results in varieties and differences (Blommaert, 2007, 2010; Machin & van Leeuwen, 2003; Pennycook, 2006). Therefore, two significant global social movements in Indonesia were chosen in this article. The first one is the social movement of Tragedi Kanjuruhan which started from specific local issues and narratives, and the second one is Global Climate Strike social movement which started from global issues shared by people worldwide. Both social movements have a specific language rhetoric. It is shown through the languages used in each social movement which reflects locality and globality. To examine this mobilization, this study employs scaling or scale measurement as a method (see sociolinguistic scales from Blommaert, 2010; scalar practice from Canagarajah & De Costa, 2016), focusing on scope and value (horizontal and vertical measurement). From the analysis, it is known that the differences in linguistic resources contribute to different elements of locality and mobility which circulates with different motives. In the end, this study can offer valuable insights into understanding how global and local are mobilized in one example of globalization.